Campaign Media Strategy: Clicks and Reposts vs Cable and Radio - Jang, Junue; Lee, ChaiHee (Technium Social Sciences Journal, 2025)
This paper examines how candidates in an election allocate campaign resources between traditional and social media using a game-theoretic framework. The dynamic between an incumbent and challenger is modeled as a strictly competitive game where the mixed-strategy Nash equilibrium is derived for a series of electoral scenarios. These scenarios touch on budget disparities, outsider and populist candidacies, and corruption scandals, stemming from a baseline model that captures incumbency bias. Results indicate that challengers consistently and stably favor social media; meanwhile, incumbents adapt their media allocation strategy in favor of social media in response to challenger benefits and harms across the two platforms. Social media’s repeated presence as the decisive arena suggests that political campaigns can no longer afford to ignore digital media in the modern era.